Penggunaan Metode Picture Exchange Communication System (PECS) Dalam Meningkatkan Kemampuan Komunikasi Verbal Anak Autis di SLB Kreasi Mandiri - Siwi, Femmy D.; Mamarimbing, Aiwa; Dapa, Aldjon N. (Peneliti.net, 2025)
This research aims to improve the verbal communication skills of autistic children so that they can more effectively express their needs, wants and feelings, develop independence in communicating with others without the need for assistance and to evaluate the impact of the PECS method in reducing the difficulties experienced by autistic children when interacting with others including behaviors that can hinder effective communication. Even though previous research has shown that the Picture Exchange Communication System (PECS) method can be effective in improving the communication skills of autistic children, there are still some gaps in research related to the use of the PECS method in improving the verbal communication skills of autistic children such as, the lack of research evaluating the impact of the PECS method in improving verbal communication skills in SLB Kreasi Mandiri. This study using single subject research method explored the effect of PECS method in improving verbal communication ability of autistic children. The results of this study indicate that the use of the PECS method has a positive impact in helping to improve the verbal communication of children with autism. Where at baseline-A1 before being given treatment got a percentage of 33%, in the intervention phase 75%, and at baseline-A2 got satisfactory results of 91%. There is a change in the value of means that initially baseline-A1 the value obtained is only 1.33 until the baseline-A2 reaches a value of 3.66 and the change in data levels between baseline-A1 and intervention (B) conditions of (+2), intervention (B) and baseline-A2 of (+3) indicates a good trend and there is no overlap of data because the percentage is 0% indicating no overlapping data, and the effect of the intervention and target behavior can be clearly observed. From the results of this study, it can be concluded that the PECS method is effective in helping autistic children develop verbal communication skills. This research is expected to contribute to SLB Kreasi Mandiri regarding communication strategies for autistic children